1998
DOI: 10.3354/dao034071
|View full text |Cite
|
Sign up to set email alerts
|

An infectious viral disease of penaeid shrimp newly found in Korea

Abstract: Since 1993, massive mortalities have occurred among the penaeid shrimp Penaeus orientalis cultured in Korea. The major gross findings of the naturally occurring cases were 2 to 6 mm sized white spots on the inside of the carapace and reddish discolorization. Amphophilic to basophillc intranuclear inclusion bodies were readily observed in the epithelia of epidermis, foregut, gills, and lymphoid organs Electron microscopy revealed enveloped and nonoccluded ellipsoid to rod-shaped virus particles within the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 3 publications
1
42
0
Order By: Relevance
“…At least 18 cultured and/or wild penaeid shrimp (Park et al, 1998), eight caridean species (Pramod-Kiran et al, 2002), seven species of lobster (Rajendran et al, 1999), seven species of crayfish (Edgerton, 2004), 38 crab species (Yoganandhan et al, 2003) six non-decapod crustacean species (Hossain et al, 2001), members of the phyla Chaetognata and Rotifera (Yan et al, 2004), polychaete worms (Supak et al, 2005) and some aquatic insect larva (Ramírez-Douriet et al, 2005) have been found susceptible to the virus. Histopathological observations during WSV infection in brief is available regarding shrimp species such as Penaes monodon (Durand et al, 1997;Wang et al, 1999Wang et al, , 2000Mishra and Shekhar, 2005) Litopenaeus vannamei and Marsupenaeus japonicus (Lu et al, 1997;Lightner et al, 1998;Escobedo-Bonilla et al, 2007;Perez et al, 2005;Pantoja and Lightner, 2003), species of Crabs (Kanchanaphum et al, 1998;Kou et al, 1998) and lobster (Rajendran et al, 1999;Wang et al, 1998;Jiravanichpaisal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…At least 18 cultured and/or wild penaeid shrimp (Park et al, 1998), eight caridean species (Pramod-Kiran et al, 2002), seven species of lobster (Rajendran et al, 1999), seven species of crayfish (Edgerton, 2004), 38 crab species (Yoganandhan et al, 2003) six non-decapod crustacean species (Hossain et al, 2001), members of the phyla Chaetognata and Rotifera (Yan et al, 2004), polychaete worms (Supak et al, 2005) and some aquatic insect larva (Ramírez-Douriet et al, 2005) have been found susceptible to the virus. Histopathological observations during WSV infection in brief is available regarding shrimp species such as Penaes monodon (Durand et al, 1997;Wang et al, 1999Wang et al, , 2000Mishra and Shekhar, 2005) Litopenaeus vannamei and Marsupenaeus japonicus (Lu et al, 1997;Lightner et al, 1998;Escobedo-Bonilla et al, 2007;Perez et al, 2005;Pantoja and Lightner, 2003), species of Crabs (Kanchanaphum et al, 1998;Kou et al, 1998) and lobster (Rajendran et al, 1999;Wang et al, 1998;Jiravanichpaisal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…WSD outbreaks were first detected in Japan and China in 1993 (Nakano et al 1994, Zhan et al 1998 and in the following years quickly spread throughout Asia (Wongteerasupaya et al 1995, Anonymous 1997, Mohan et al 1998, Park et al 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Mortality rates are usually very high and cumulative mortality can reach 100% within 3 to 10 d from the onset of visible gross signs (Chou et al 1995, Wongteerasupaya et al 1995. White spot disease has been reported from several Asian countries since the early 1990s (Inouye et al 1994, Momoyama et al 1994, Nakano et al 1994, Chou et al 1995, Flegel et al 1995, Huang et al 1995, Wongteerasupaya et al 1995, Mohan et al 1998, Park et al 1998, Y. G. Wang et al 1999, and more recently from South America and from the south-eastern coast of the USA (Lightner et al 1997, Lo et al 1999, Q. Wang et al 1999.…”
mentioning
confidence: 99%
“…All the major species of cultivated penaeid shrimp can be naturally infected by this virus (Inouye et al 1994, Nakano et al 1994, Chou et al 1995, Wongteerasupaya et al 1995, Lo et al 1996, Flegel 1997, Lightner et al 1997, Mohan et al 1998, Nunan et al 1998, Park et al 1998, Q. Wang et al 1999. In addition to penaeid species, both natural and experimental infections have also been reported in caridean shrimp (Exopalaemon orientalis and Macrobrachium rosenbergii), crayfish (Orconectes punctimanus), wild crabs (Calappa lophos, Portunus sanguinolentus, P. pelagicus, Charybdis sp., Helice tridens and Scylla serrata), wild lobsters (Panulirus sp.…”
mentioning
confidence: 99%